Pulmonary Valve Replacement in Repaired Tetralogy of Fallot: Midterm Impact on Biventricular Response and Adverse Clinical Outcomes - He, Fengpu; Feng, Zicong; Yuan, Jianhui; Ma, Kai; Yang, Keming; Lu, Minjie; Zhang, Sen; Li, Shoujun (Frontiers in Pediatrics, 2022)
Background: Pulmonary regurgitation (PR), though well tolerated for the short term in patients with repaired tetralogy of Fallot (rTOF), could lead to right ventricular (RV) dysfunction, arrhythmias, and sudden cardiac death. Pulmonary valve replacement (PVR), as the gold-standard treatment for PR, is performed to mitigate these late effects. We aimed to evaluate the midterm outcomes and predictors of adverse clinical outcomes (ACO). Methods: From May 2014 to December 2017, forty-two patients with rTOF undergoing surgical or transcatheter PVR in our department were retrospectively included. Cardiovascular magnetic resonance was performed before PVR (pre-PVR), early after PVR (early post-PVR), and midterm after PVR (midterm post-PVR). Medical history and individual data were collected from medical records. ACO included all-cause death, new-onset arrhythmia, prosthetic valve failure, and repeat PVR. Results: The median follow-up duration was 4.7 years. PVR was performed at a median age of 21.6 years. There was no early or late death. Freedom from ACO at 3 and 5 years was 88.1%  5% and 58.2%  9%, respectively. RV end-diastolic volume index (RVEDVI) and end-systolic volume index (RVESVI) significantly reduced early after PVR and further decreased by midterm follow-up (pre-PVR vs early post-PVR vs midterm post-PVR: RVEDVI, 155.2  34.7 vs 103.8  31.2 vs 95.1  28.6 mL/m2, P<0.001; RVESVI, 102.9  28.5 vs 65.4  28.2 vs 57.7  23.4 mL/m2, P<0.001). Multivariable analysis revealed that the occurrence of ACO was significantly increased in patients with lower left ventricular end-systolic volume index. Conclusions: A significant reduction of RV volume occurred early after PVR, followed by a further improvement of biventricular function by midterm follow-up. The midterm freedom from ACO was favorable.